Student Management as an Effort to Improve Character Education - Istiqomah; Nursofah (Jurnal Manajemen Pendidikan, 2024)
Background The phenomenon of character degradation of students at various levels is a serious challenge for the world of education today. Advances in technology and information, as well as changes in social values, often cause negative behavior that affects the development of their character. Purpose This study aims to explore in depth the management of students in improving children's character education. Design/method/approach The method used in this study is a literature review, by reviewing various relevant academic sources, such as books, journal articles, and education policy documents. Results The results of the study show that planned and systematic student management, including behavioral supervision, counseling guidance, the formation of a conducive learning environment, and the involvement of parents and the community, contribute significantly to the formation of children's character. A collaborative approach between teachers, parents, and the social environment has also been shown to strengthen character values such as responsibility, discipline, and tolerance. Contribution/value The implications of this study indicate that character education is not only the responsibility of individual educators, but also requires systemic support from the entire education ecosystem. The implementation of holistic student management-based policies is expected to produce a generation that is not only academically intelligent, but also has a strong character.